An Analysis of Teacher’s Strategies in Teaching Writing on Recount Text in Pandemic Through Online Class at the tenth Grade of SMA Negeri 1 Kolang - Rajagukguk, Rosdiana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2023)
This study is about An Analysis of Teachers Strategies In Teaching Writing Recount Text In Pandemic Through Online Class. The objective of this study was to know how the strategies used by teachers in the classroom recount texts in pandemics through an online class at Tenth Grade of SMA Negeri1 Kolang. This study was conducted by applying Descriptive Qualitative research. The writer recorded 2 English teachers' strategies to get the data. The instrument of collecting data was Observation, Interview, and Documentation. The data were obtained on English teachers' Strategies in teaching recount text in pandemics through online classes. The writer found there were Strategies of the English teachers in teaching recount text through online classes. The findings of data analysis showed that strategies used by the English teachers in teaching recount text in pandemic through online class are (1) Explanation about the recount text, (2) Deep explanation (send a link video about the material by WhatsApp group to deep understand about recount text), (3) Quiz about recount text, then (4) Give the students exercise about recount text. The benefits of this research for state and nation especially for English teachers are this research is used as a source by teachers to implement strategies in teaching writing through an online class.